Non-retrobulbar anaesthesia for trabeculectomy (1995)
A prospective clinical trial using sub-conjunctival (Sub- Tenon's) anaesthesia for trabeculectomy is reported. Forty-one eyes of 22 consecutive patients with glaucoma had trabeculectomy performed using the sub-conjunctival method of local anaesthesia. The effectiveness of the anaesthetic, intra-operative and post-operative complications were recorded. Sub-conjunctival injection of local anaesthesia was found to be painless and free from the complications associated with retrobulbar injections. Surgery was also found to be easier as a conjunctival bleb was already raised allowing easy access to the sub-conjunctival space. Voluntary eye movements remained but did not interfere with surgery.